Bovine respiratory disease: treatment outcomes, prevalence of antimicrobial resistance and systematic review of control methods - Neal, Kyndall Brooke (Kansas State University, 2024)
Bovine respiratory disease (BRD) is an economically important disease in feedyards influencing both animal welfare and use of antimicrobials. While much research has been completed there are still knowledge gaps regarding the treatment plans and optimal ways to manage cattle with BRD. The objective of the first chapter of the thesis was to identify potential associations between nasopharyngeal microbiota and antimicrobial resistance patterns of clinical cases that lived or died compared to non-diseased controls. Enrolled animals were subdivided based on clinical disease status and case outcome (subsequent mortality or finishing the feeding phase). Deep nasopharyngeal swabs were collected from enrolled animals and submitted for bacterial isolation, antimicrobial susceptibility determination, and metagenomics analysis. Enrolled cattle were represented in three groups: animals at first treatment for BRD that subsequently died (BRDM, n=9), animals at first treatment for BRD that subsequently lived (BRDL, n=15), and animals that were never treated for BRD during the feeding phase (CONT, n=11). Antimicrobial resistance patterns for Pasteurella multocida illustrated that cattle in each outcome category had isolates that were pan-susceptible or only showing resistance to oxytetracycline. Nasal metagenomics analysis showed relative abundance of species and genera with few differences among the three outcomes. Higher alpha diversity was identified in BRDL compared to CONT at the species level and both BRDL and BRDM showed increased alpha diversity compared to CONT at the genera level. Overall, this work illustrated nasopharyngeal microbiota showed relatively few differences among BRD cases that lived or died compared to animals without BRD. The second chapter objective was to identify potential relationships between risk factors known at the time of initial BRD treatment with three post-treatment outcomes: first treatment success (FTS; finishing feeding phase with no further treatments), non-cause specific case fatality risk (CFRALL; post-treatment mortalities from any cause), and cause-specific case fatality risk (CFRBRD; mortalities attributed to BRD). This retrospective analysis used generalized linear mixed models to evaluate relationships between covariates of interest (arrival: sex, weight, month; treatment event: days-on-feed (DOF), rectal temperature, day-of-week, antibiotic drug class) with each outcome (FTS, CFRALL, CFRBRD). Analysis included 132,521 individual-animal initial BRD treatment records from 14 central U.S. feedyards (May 2017 to Dec 2020) with overall FTS of 67.8%, CFRALL of 10.0%, and CFRBRD of 6.3%. The FTS was associated (P < 0.05) with all covariates except sex, CFRALL was associated with all covariates, and CFRBRD was associated with all covariates except day-of-week treated. Treatment early in the feeding phase (DOF 0-10, 11-20) was associated with lower FTS (49.2% ± 0.8; 55.3% ± 0.8), higher CFRALL (12.5% ± 1.3; 12.6% ± 1.4) and higher CFRBRD (6.3% ± 1.1; 6.1% ± 1.0) compared to cattle treated on days 21-70. Rectal temperature in the 39.4-40.0°C category had higher CFRALL (15.3% ± 1.5) and CFRBRD (9.2% ± 1.5) compared to other rectal temperature categories. Increased knowledge of risk factors associated with treatment outcomes has the potential to help inform therapeutic decisions. This systematic review in the third thesis chapter sought to identify published information relative to antimicrobial use in BRD control and metaphylaxis. Specific research questions addressed case fatality risks, first treatment success, switching drug classes between treatments, switching drug classes between metaphylaxis and first treatment, post-metaphylactic or post-treatment intervals, as well as concomitant therapies. Databases searched included PubMed, CAB Direct, and Agricola, resulting in 418 publications meeting the search criteria. Manuscripts were then sorted into topic categories for review. Case fatality risk decreases with treatments of tulathromycin when compared to other antimicrobials. Similar trends were seen with first treatment success and included other macrolides as well, resulting in higher success. Studies showed longer post-treatment intervals had better morbidity resolution when compared to shorter post-treatment intervals. No prospective manuscripts were found regarding switching drug classes between metaphylaxis and first treatment or first and subsequent treatments. The research that evaluated concomitant therapy for BRD treatment did not show an advantage compared to single-antimicrobial treatment. This literature review identified several knowledge gaps related to specific application methods of treatment; and more research in these areas could be conducted to understand the optimal management practices and treatment strategies for BRD in cattle. By looking into more treatment options and outcomes there is hope to improve future BRD treatment outcomes. While much remains to be learned, research is always being conducted and new information leading to BRD successes can be found.
Keywords: Bovine respiratory disease; Antimicrobials; Antimicrobial resistance; Cattle